A cholestatic pattern predicts major liver‐related outcomes in patients with non‐alcoholic fatty liver disease. (12th March 2022) - Pennisi, Grazia; Pipitone, Rosaria Maria; Cabibi, Daniela; Enea, Marco; Romero‐Gomez, Manuel; Viganò, Mauro; Bugianesi, Elisabetta; Wong, Vincent Wai‐Sun; Fracanzani, Anna Ludovica; Sebastiani, Giada; Berzigotti, Annalisa; Di Salvo, Francesca; et al.
Abstract: Background & Aims: NAFLD patients usually have an increase in AST/ALT levels, but cholestasis can also be observed. We aimed to assess in subjects with NAFLD the impact of the (cholestatic) C pattern on the likelihood of developing major liver‐related outcomes (MALO). Methods: Five hundred and eighty‐two consecutive patients with biopsy‐proven NAFLD or a clinical diagnosis of NAFLD‐related compensated cirrhosis were classified as hepatocellular (H), C and mixed (M) patterns, by using the formula (ALT/ALT Upper Limit of Normal‐ULN)/(ALP/ALP ULN). MALO were recorded during follow‐up. An external cohort of 1281 biopsy‐proven NAFLD patients was enrolled as validation set. Results: H, M and C patterns were found in 153 (26.3%), 272 (46.7%) and 157 (27%) patients respectively. During a median follow‐up of 78 months, only 1 (0.6%) patient with H pattern experienced MALO, whilst 15 (5.5%) and 38 (24.2%) patients in M and C groups had MALO. At multivariate Cox regression analysis, age >55 years (HR 2.55, 95% CI 1.17–5.54; p  = .01), platelets <150 000/mmc (HR 0.14, 95% CI 0.06–0.32; p  < .001), albumin <4 g/L(HR 0.62, 95% CI 0.35–1.08; p  = .09), C versus M pattern (HR 7.86, 95% CI 1.03–60.1; p  = .04), C versus H pattern(HR 12.1, 95% CI 1.61–90.9; p  = .01) and fibrosis F3–F4(HR 35.8, 95% CI 4.65–275.2; p  < .001) were independent risk factors for MALO occurrence. C versus M pattern(HR 14.3, 95% CI 1.90–105.6; p  = .008) and C versus H pattern (HR 15.6, 95% CI 2.10–115.1; p  = .0068) were confirmed independently associated with MALO occurrence in the validation set. The immunohistochemical analysis found a significantly higher prevalence of moderate‐high‐grade ductular metaplasia combined with low‐grade ductular proliferation in C pattern when compared with the biochemical H pattern. Gene expression analysis showed a lower expression of NR1H3, RXRα and VCAM1 in patients with the C pattern. Conclusions: The presence of a cholestatic pattern in patients with NAFLD predicts a higher risk of MALO independently from other features of liver disease.